Analysis of the Similarities and Differences Between Two Education-Based Films from the Perspective of Speech Acts - Abdullah, Wan Nor Azlina; Kazim, Mohamad Rozi (Jurnal Pendidikan Bitara UPSI, 2024)
This research involves the analysis of similarities and differences between two educational films from the perspective of speech acts. Speech acts are utterances that have meaning according to a specific context. This research aims to describe the similarities and differences in the speech acts uttered between the film ’Adiwiraku’ and the film ’Yek Icin Mahak’. The research design is qualitative, involving content analysis of the speech text in the dialogues related to Searle’s (1969) speech act theory and library research methods to obtain more in-depth information. This study involves two educational films, namely ’Adiwiraku’ and ’Yek Icin Mahak’. The findings show that there are similarities and differences in the speech acts in both films, observable from various aspects not only in terms of categories and subcategories but also involving the use of sentences, words, language, intonation, social status, vocabulary, regional and environmental factors, students’ backgrounds and the subjects taught by the teachers. This indicates that there is a comparison in terms of speech even though both films are educational. Overall, this study is hoped to help individuals better understand the meaning behind the uttered speech.